Assessment of Mothers’ Knowledge regarding to Dehydration in Children under 5 Years at Pediatric Hospital in Kirkuk City - Eman Abbass Ahmed Mona Jihad Saeed (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:Dehydration frequently complicates illnesses often seen in children arriving at the emergency department. It entails the excessive depletion of water and bodily fluids, reduced intake, heightened output, fluid redistribution, and leakage of fluids from capillaries. Objective: The object of the study is to assess to identify mothers’ knowledge toward Management of dehydration in children and to find out the relationship between the level of knowledge of these mothers with selected demographic variables. Methods:A Descriptive non-experimental study, it was carried out atpediatrichospital in Kirkuk city, samples includes mothers who attendedto pediatric hospital. The study samples were chosen by non-probability sampling (purposive sample). An instrument was constructed as a questionnaire for the study purpose,the questionnaire consist of (2) domains (General information, concepts and facts about dehydration in children and Management of dehydration in children). Result: Shows that (31.7%) mothers were ages between (21-25 years), (60%) were housewives, and (31.7%) of mothers had Intermediate school education. Most of the mothers didn’t participate in training courses about dehydration and (51.7%) of them with no previous experiences about caring of a child with dehydration. Conclusion: The study concluded that, mothers’ knowledge about dehydration is fair.